Field screening for drought tolerance in Setaria italica and Panicum miliaceum millet germplasm from Iran - Nejad, Ghasem Mohammadi; Hossein, Vaezi; Eslam, Majidi-Heravan; Babak, Nakhoda; Farokh, Darvish-Kajouri (The Indian Journal of Genetics and Plant Breeding, 2017)
The present study aims at field screening of Proso and Foxtail millet ecotypes for drought tolerance. Accordingly, 96 promising millet ecotypes along with four checks were evaluated under field conditions in Yazd province of Iran. Field experiment was conducted using an incomplete block design (LATTICE) with two replications under drought stress and control conditions in a period of two years. Multivariate analyses showed variance significant genetic variation (P < 0.01) among millet ecotypes of Iranian origin. Drought stress tremendously affected grain yield of all genotypes. The interaction between genotype and drought was significant for panicle weight, panicle length and days to flowering. Based on the results of multivariate analyses we identified the effective traits which are the foremost factor responsible for grain yield and dry weight of fodder under drought stress. Therefore, the selection based on these traits would be preferable to identify genotypes with high yield. Eventually, eight ecotypes with the higher grain yield and 8 with the higher dry weight fodder were found highly adoptive under moisture stress conditions. Such ecotypes can be recommended as promising genotypes which may eventually be released as new cultivars for drought-affected areas.